RESULTS OF EXPERIMENTAL STUDIES OF THE CHILDREN’S AXIAL PUMP «DON-3» - G. P. Itkin; O. Yu. Dmitrieva; A. S. Buchnev; A. A. Drobyshev; A. P. Kuleshov; A. V. Volkova; T. A. Halilulin (Вестник трансплантологии и искусственных органов, 2018)
Aim. To evaluate the functioning of an implantable pediatric axial pump «DON-3» for bypassing the left ventricle of the heart in experiments on sheep.Materials and methods. Five sheeps at the age of 12–18 months performed paracorporeal installation of the children’s axial pump «DON-3» according to the scheme «left ventricle – aorta».Results. A technique was developed and 5 chronic experiments were conducted on sheep to assess the model of the children’s axial pump «DON-3». The duration of the experiments in this series averaged 9 ± 5 days. The main indicators of hemodynamics, acid-base balance were within the norm. Conducted morphological and histological studies of the kidneys, liver and lungs did not reveal the presence of zones of ischemia and thromboembolism.Conclusion. The results of this series of experiments showed satisfactory results, suggesting further research on the development of prototypes of a pediatric pump for clinical practice.